2010
DOI: 10.1128/jvi.02545-09
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Facilitate Recovery from Venezuelan Equine Encephalitis Virus-Induced Encephalomyelitis in the Absence of Antibody

Abstract: Venezuelan equine encephalitis virus (VEEV) is a mosquito-borne RNA virus of the genusAlphavirus that is responsible for a significant disease burden in Central and South America through sporadic outbreaks into human and equid populations. For humans, 2 to 4% of cases are associated with encephalitis, and there is an overall case mortality rate of approximately 1%. In mice, replication of the virus within neurons of the central nervous system (CNS) leads to paralyzing, invariably lethal encephalomyelitis. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 63 publications
(82 reference statements)
2
40
0
Order By: Relevance
“…Nonetheless, antibody response appeared to be dispensable for clearance of VEEV from CNS [231]. In addition, antibody response was not required for recovery of μMT mice from encephalomyelitis induced by attenuated strains of VEEV [232], such that these mice were able to reduce dramatically virus titers in the CNS and clear virus from CSF, in the absence of antiviral antibody.…”
Section: Viral Clearance From the Cnsmentioning
confidence: 94%
See 1 more Smart Citation
“…Nonetheless, antibody response appeared to be dispensable for clearance of VEEV from CNS [231]. In addition, antibody response was not required for recovery of μMT mice from encephalomyelitis induced by attenuated strains of VEEV [232], such that these mice were able to reduce dramatically virus titers in the CNS and clear virus from CSF, in the absence of antiviral antibody.…”
Section: Viral Clearance From the Cnsmentioning
confidence: 94%
“…CD4 T cells are also required for protection against infection with other arboviruses, including JEV [237], yellow fever virus [244], TBEV [242], RVFV [229], and VEEV [231]. CD4 Tcell response resulted in a dramatic reduction of virus titers in the CNS and mediated full recovery of μMT mice from VEEV-induced encephalomyelitis [232].…”
Section: Viral Clearance From the Cnsmentioning
confidence: 99%
“…Mechanistic studies demonstrated that artificial attenuation of EEE results in a marked increase in sensitivity to type I IFN associated with decreased virulence of the virus (Aguilar, et al, 2005;Brown & Officer, 1975;Brown, et al, 1975;Gardner, et al, 2009;Murphy, 1975;Wagner, 1963). Combined with studies in WEE, this led researchers to hypothesize that differences in disease presentation and incidence in humans between South American and North American isolates could be attributed to IFN sensitivity (Brown & Officer, 1975;Brown, et al, 1975). Indeed, comparison of replication of North American and South American strains in IFN pre-treated Vero cells showed a depressive effect on replication of the South American isolates.…”
Section: Innate Immune Response To Eeementioning
confidence: 99%
“…Chimeric vaccines of EEE and WEE have also been proposed as have trivalent vaccines utilizing immunogens from all three encephalitic alphaviruses or recombinant genetic systems (Atasheva, et al, 2009;Barber, et al, 1978;Pedersen, 1976;Schoepp, et al, 2002). In murine models with pre-existing immunity generated via vaccination, neutralizing antibody is typically detected ten days following infection (Brown & Officer, 1975;Brown, et al, 1975). Neutralizing antibody also develops in the spinal fluid of rabbits vaccinated with either a live or formalin-inactivated vaccine, and such animals are able to resist vigorous challenge routes by IC injection of active virus.…”
Section: Antibody Responsementioning
confidence: 99%
See 1 more Smart Citation